PENERAPAN ARSITEKTUR BIOPHILIC PADA PERANCANGAN WISMA ATLET DI KOTA MAKASSAR - Saha, Riska (Universitas Gorontalo, 2024)
Abstract_ Makassar City is one of the largest cities in Indonesia, currently experiencing rapid development in the field of sports. Makassar City does not yet have athlete's guesthouse facilities based on the journal Study of Athlete's Homestead Facility Development (Azis Alimuddin, 2016), which is one of the important supporting facilities for sports activities as a resting place for athletes to unwind. This Athlete's Home Design Concept adopts Biophilic as an approach. The Biophilic concept can be applied by: creating a green garden or yard in the residential yard, increasing the number of openings for natural ventilation and lighting, planting plants indoors, using natural materials, making the building look magnificent so that it can raise the spirit, creating a pond or lake to complement the atmosphere. blending with nature, processing the site flexibly so that the site atmosphere is not stiff.Â Â